1989
DOI: 10.1177/000348948909800412
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Transbronchial Needle Aspiration for the Diagnosis of Sarcoidosis

Abstract: To determine the value of transbronchial needle aspiration biopsy in the diagnosis of sarcoidosis, we reviewed a 1-year experience of consecutive patients with sarcoidosis presenting with hilar and/or paratracheal adenopathy. The sensitivity of transbronchial needle aspiration biopsy in obtaining specimens of noncaseating granulomas was 90%. This yield exceeds that of most published reports of transbronchial lung biopsy and bronchial mucosal biopsy and suggests that transbronchial needle aspiration biopsy may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 10 publications
1
40
0
5
Order By: Relevance
“…ACCP 2013 guideline for lung cancer found a mean pooled sensitivity of C-TBNA as 78%, ranging from 14 to 100% in terms of lung cancer (3). Studies including patients with suspicion of sarcoidosis have diagnostic sensitivities ranging from 72 to 90% (10)(11)(12). In a study including 34 patients, C-TBNA revealed a definite diagnosis in 14 patients (41.1%) and C-TBNA had a higher DY for malignancy (64.7%) compared to non-malignant diseases (17.6%) (13).…”
Section: Discussionmentioning
confidence: 99%
“…ACCP 2013 guideline for lung cancer found a mean pooled sensitivity of C-TBNA as 78%, ranging from 14 to 100% in terms of lung cancer (3). Studies including patients with suspicion of sarcoidosis have diagnostic sensitivities ranging from 72 to 90% (10)(11)(12). In a study including 34 patients, C-TBNA revealed a definite diagnosis in 14 patients (41.1%) and C-TBNA had a higher DY for malignancy (64.7%) compared to non-malignant diseases (17.6%) (13).…”
Section: Discussionmentioning
confidence: 99%
“…The patients usually undergo transbronchial parenchymal tissue biopsy and one study has shown these biopsies to have a diagnostic adequacy of 70% with sensitivity increasing with higher number of samples (14). Many studies have shown that the conventional TBFNAC method has similar adequacy rates, and there are reports of high sensitivity rates such as 90% (15)(16)(17)(18)(19). The biggest advantage of TBFNAC method when compared with transbronchial parenchymal tissue biopsy method is that the morbidity rate is low and potential complications such as pneumothorax and bleeding are encountered less often.…”
Section: Methodsmentioning
confidence: 99%
“…Hem mediastinoskopi gibi invaziv bir işlemin aksine ayaktan takip edilen hastalara uygulanabilir olması hem de mediastinal lenf bezlerinin yanı sıra hiler lenf bezlerinden de örnekleme yapılmasına fırsat sağlaması bakımından oldukça avantajlı bir yöntem hâline gelmiştir. 11,17,25,[34][35][36] Diğer taraftan, mediastinoskopideki kadar büyük biyopsi materyali alınamadığı için tanısallığı sitoloğun tecrübesine de bağlıdır. TBİA tanısallığı ile ilişkili olarak yapılan çalışmalarda endobronşiyal ultrasonografi (EBUS) eşliğinde alınan biyopsilerin tanı oranları daha yüksek bulunmuş olup, farklı çalış-malarda %60,9-90,3 arasında saptanmıştır.…”
Section: Bulgularunclassified